2019
DOI: 10.1038/s41598-018-36457-2
|View full text |Cite
|
Sign up to set email alerts
|

Precision of a Novel Craniofacial Surgical Navigation System Based on Augmented Reality Using an Occlusal Splint as a Registration Strategy

Abstract: The authors have developed a novel augmented reality (AR)-based navigation system (NS) for craniofacial surgery. In this study, the authors aimed to measure the precision of the system and further analyze the primary influencing factors of the precision. The drilling of holes into the mandibles of ten beagle dogs was performed under the AR-based NS, and the precision was analyzed by comparing the deviation between the preoperational plan and the surgical outcome. The AR-based NS was successfully applied to qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…For instance, Pietruski et al [10] reported errors of 4.2 ± 1° and 5.4 ± 3.9° in sagittal and frontal osteotomy planes and Viehöfer et al [33] found similar errors of 4.9 ± 4.2°. Smaller errors of 2 ± 1.2° and 1.3 ± 1.2° were reported in recent studies [34,35]. In our study, only 30.2% of cases presented ≤ 2° inclination angle errors (Table 2).…”
Section: Error In the Position And Dimensions Of The Virtual Modelssupporting
confidence: 49%
“…For instance, Pietruski et al [10] reported errors of 4.2 ± 1° and 5.4 ± 3.9° in sagittal and frontal osteotomy planes and Viehöfer et al [33] found similar errors of 4.9 ± 4.2°. Smaller errors of 2 ± 1.2° and 1.3 ± 1.2° were reported in recent studies [34,35]. In our study, only 30.2% of cases presented ≤ 2° inclination angle errors (Table 2).…”
Section: Error In the Position And Dimensions Of The Virtual Modelssupporting
confidence: 49%
“…The spatial information embedded in medical three‐dimensional (3D) images is being increasingly used to personalize treatment by means of computer‐assisted surgery (CAS) . This new field of medicine encompasses virtual surgical planning, 3D printing of personalized constructs, such as anatomical models, surgical saw guides, or implants, virtual and augmented reality and robot‐guided surgery . The use of such emerging technologies in medicine has resulted in better treatment outcomes and a reduction in both operating times and costs .…”
Section: Introductionmentioning
confidence: 99%
“…The dentition may be used as a reference in a direct or indirect way in Augmented Reality (AR) [34][35][36] . Wang et al designed a method in which an intra-oral scan is matched to the CT scan (based on an Iterative Closest Point approach) 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of the dentition, within the field-of-view, is a requirement for the workflow. Jiang et al have proposed an AR workflow resembling the registration-free workflow described in this study 34 . An intra-oral scan of the gypsum cast with the DRF in place is acquired, and the resulting model is matched to the CT scan using user-indicated landmarks on the dental cusps in the CT model and intra-oral scan.…”
Section: Discussionmentioning
confidence: 99%